A Roundness Machine Measuring Probe Calibration - Vit, Jiri; Novak, Martin (Manufacturing Technology Journal, 2018)
The article deals with the research of the measuring probe signal of roundness machine Roundscan of Jenoptik IM producer. The probe of this machine scans geometric form as well as surface structure. The probe signal dependence on the probe arm elevation is not perfect linear and this influences the precision of evaluated form characteristics, roughness parameters as well as drall parameters. A quantification of calibration way influence on the signal characteristic was main research task. A calibration process simulator was designed and built in MATLAB for this. This article describes a way of obtaining of real probe signal. Metrological filters according current standards ISO 16610-21 and ISO 16610-22 were built in MATLAB for obtained signal filtering. The calibrating simulator simulated various master standard values, various probe arm starting positions before the calibration, various probe arm starting positions before subsequent common measurement, and tolerance limit utilisation during a master standard value transmission to the probe signal. An efficiency of signal linearization procedure was explored, as well. Obtained results are presented as signal zones, which delimit assigned signal deviations from perfect signal characteristic.
Keywords: surface structure; probe signal; calibration; roundness machine